The Log of a Privateersman - Collingwood, Harry, 1851-1922; Rainey, W. (William), 1852-1936 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Log of a Privateersman" by Harry Collingwood is a novel written in the early 20th century. This maritime adventure story details the exploits of a young sailor named George Bowen, who aspires to a life of fortune and fame on the high seas during the Napoleonic Wars. Through Bowen's eyes, readers experience the dangers and thrills of privateering, where he seizes opportunities amidst battles and encounters with enemy ships. At the start of the tale, the narrative unfolds with an audacious French raid leading to the capture of a British trader, the "Weymouth". As the plot develops, we meet George and learn of his commendable qualities as a sailor, along with his aspirations when he is offered a lucrative position as second mate on a new privateer, the "Dolphin". The opening chapters vividly capture the anticipation of adventure, depicting George's interactions with his family, his profound excitement for the sea, and the brewing unrest of war, setting the stage for his journey as a privateersman where fortune awaits him. Central to this narrative is George's determination, the camaraderie among the crew, and the unfolding series of naval encounters that promise action and intrigue. (This is an automatically generated summary.)
Release date is 2007-04-13
Produced by Nick Hodson of London, England
Keywords: Orphans -- Juvenile fiction; Conduct of life -- Juvenile fiction; Adventure stories; Voyages and travels -- Juvenile fiction; Seafaring life -- Juvenile fiction; Sailors -- Juvenile fiction; Prisoners -- Juvenile fiction; Privateering -- Juvenile fiction; Great Britain -- History, Naval -- 19th century -- Juvenile fiction